ANALISIS KESALAHAN SISWA MTs DALAM MENYELESAIKAN SOAL PADA MATERI TEOREMA PYTHAGORAS - Annisa Siti Rohmah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to describe the mistakes made by students in solving mathematical problems in the pythagorean theorem material. This study is a qualitative study with 23 selected students from class VIII A in MTs Al-Mukhtariyah Mande Academic Year 2019/2020. Data collection instruments using description tests. Data analysis in this study was taken in the form of pictures and paragraphs to draw conclusions. After conducting research and reducing data, it is obtained that the most common mistakes made by students are lack of understanding the concept of the Pythagorean theorem, lack of understanding of the language of questions, in working on questions less thoroughly, and finally students lack understanding of problems when related to daily life. Good mastery of the concept of material is able to bring students in producing a good solution as well. Understanding the concepts and understanding of principles must be mastered by students to facilitate working on the problems presented.